1997
DOI: 10.1590/s0004-282x1997000300016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidermal growth factor on the [3H]-thymidine uptake in the SK-N-SH and SH-SY5Y human neuroblastoma cell lines

Abstract: The studies on the factors that regulate the biology of the neuroblastoma cell lines may offer important information on the development of tissues and organs that derive from the neural crest. In the present paper we study the action of epidermal growth factor (EGF) on two human neuroblastoma cell lines: SK-N-SH which is composed at least of two cellular phenotypes (neuroblastic and melanocytic/glial cells), and its pure neuroblastic subclone SH-SY5Y. The results show that EGF (10 ng/ml) significantly stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…FGF can increase the expression of p75NTR in CHP100 human neuroblastoma cells as well (Taiji et al, 1992), which as mentioned previously, could actually promote apoptosis. EGF can enhance [3H]-thymidine uptake in SK-N-SH, but not SH-SY5Y cells, and only in the presence of fetal bovine serum, suggesting the need for other serum factors to produce a proliferative response (da Motta et al, 1997). Collectively, these reports coupled with the findings from the current study, indicate that while many growth factors play a role in growth and differentiation of SH-SY5Y cells, IGF-I provides the most potent protection against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…FGF can increase the expression of p75NTR in CHP100 human neuroblastoma cells as well (Taiji et al, 1992), which as mentioned previously, could actually promote apoptosis. EGF can enhance [3H]-thymidine uptake in SK-N-SH, but not SH-SY5Y cells, and only in the presence of fetal bovine serum, suggesting the need for other serum factors to produce a proliferative response (da Motta et al, 1997). Collectively, these reports coupled with the findings from the current study, indicate that while many growth factors play a role in growth and differentiation of SH-SY5Y cells, IGF-I provides the most potent protection against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…1997). Other effects, such as EGF‐induced [ 3 H]‐thymidine incorporation, have also been described in SK‐N‐SH but not SH‐SY5Y cells (da Motta et al . 1997).…”
Section: Discussionmentioning
confidence: 97%
“…This result is intriguing because SK‐N‐SH is the parent cell line of the SH‐SY5Y cell line used in this study. However, the SK‐N‐SH cell line is composed of at least two cellular phenotypes (neuroblastic amd melanocytic/glial cells), while SH‐SY5Y is a pure subclone of the neuroblastic phenotype (da Motta et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…113 daMotta et al showed that EGFR ligand, EGF, treatment of SK-N-SH neuroblastoma cells resulted in cell proliferation. 114 Ho and colleagues confirmed these findings, but found that the EGF-stimulated proliferation was the result of EGFR activation of the PI3K/AKT pathway. 112 Tamura et al showed that gefitinib (Table 1), an EGFR tyrosine kinase inhibitor, induced apoptosis in neuroblastoma cells.…”
Section: Neuroblastoma and Growth Factorsmentioning
confidence: 92%